Avaliação de parâmetros da fermentação e da destilação para adequação dos teores de compostos secundários em aguardente de banana - Raquel Mendonca Alvarenga (2011)
This study aimed to evaluate the conditions of fermentation and distillation in banana spirit production, aiming at the adequacy of secondary compounds in relation to legislation. The four yeast strains`s fermentative potential was evaluated in banana juice. It also evaluated the steps in the production process: enzymatic hydrolysis, filtration and agitation of flasks during fermentation with different initial levels of reducing sugars (100, 120 and 150 gL-1). Spirits were produced with two banana varieties (prata and nanica) in a pilot scale. Were conducted an sorption with a activated charcoal in order to evaluate the reduction of unwanted volatile compounds. In a distillation study, were tested single and double distillation, and the secondary compounds were quantified as required by Brazilian law, in nine fractions during the distillation process. The banana spirit produced were evaluated by sensory acceptance test. Among the yeast strains evaluated, the best results were obtained using the strain Unicamp V1 and wet pressed yeast. It was verified the importance and necessity of using the steps of enzymatic hydrolysis and filtration of banana pulp to increase the ethanol yield and reducing the formation of methanol and higher alcohols. The higher concentration of sugar used (150 g L-1) showed better ethanol yield and efficiency of conversion of sugars into alcohol. Spirits produced compounds (methanol, higher alcohols, copper) in amounts above those permitted by Brazilian law. The activated charcoal was effective in reducing toxic compounds, but should be used with caution because compounds responsible for aroma and flavor of beverage are also removed in quantities that may detract the beverage. Among the two distillation techniques evaluated, the best results, with reduction of undesirable compounds in banana spirit, were found using the double distillation. The acceptance test results indicated the need of improvements the production of the banana spirit for greater acceptance or the tests be performed with panelists who are regular consumers of such spirt.